2004
DOI: 10.1002/cbic.200300769
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Studies on the Corticotropin Releasing Factor Antagonist Astressin, leading to a Minimal Sequence necessary for Antagonistic Activity

Abstract: Corticotropin Releasing Factor (CRF) antagonists are considered promising for treatment of stress-related illnesses such as major depression and anxiety-related disorders. We report here the design, synthesis and biological evaluation of 91 truncated astressin analogues in order to deduce the pharmacophoric amino acid residues. Such truncated peptides may serve as valuable lead structures for the development of new small, non-peptide-based CRF antagonists. N-Terminal truncation of astressin led to active CRF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…On the one hand, structureactivity studies of the CRF family ligands showed that the first six residues of the N-terminal portion of the peptide are not necessary for receptor signaling as long as ␣-helicity is maintained (3, 4, 16 -18). On the other hand, the C-terminal (ϳ15) residues contribute significantly to receptor binding affinities (16,19). Similar data, both on signaling and binding properties, have been reported for the other members of the B1 GPCR family and their corresponding ligands (20 -24).…”
supporting
confidence: 76%
“…On the one hand, structureactivity studies of the CRF family ligands showed that the first six residues of the N-terminal portion of the peptide are not necessary for receptor signaling as long as ␣-helicity is maintained (3, 4, 16 -18). On the other hand, the C-terminal (ϳ15) residues contribute significantly to receptor binding affinities (16,19). Similar data, both on signaling and binding properties, have been reported for the other members of the B1 GPCR family and their corresponding ligands (20 -24).…”
supporting
confidence: 76%
“…These data are reflected in the 20 conformers representing the 3D structure of ECD1-CRF-R2␤-astressin complex for which continuous helical hydrogen bonds are observed from CO i to NH iϩ4 for residues 27-37 of astressin. The C-terminal four residues prefer to be in a 3 10 -helical conformation, which is supported by the presence of ␣H i -HN iϩ2 NOEs and the missing Nle-38(␣H)-Ile-41(␤H) NOE (SI Fig. 5B).…”
Section: D Structure Of Ecd1 Of Crfr-2␤ In Complex Withmentioning
confidence: 72%
“…5B). The preference for a 3 10 helix over an ␣-helix toward the C terminus of helical peptides and proteins is often reported (26). Of special interest are the hydrogen bonds between the carbonyl of Glu-39 and the C-terminal NH 2 group, and between the carbonyl of Ile-41 and the amide of Val-113 of ECD1.…”
Section: D Structure Of Ecd1 Of Crfr-2␤ In Complex Withmentioning
confidence: 99%
See 2 more Smart Citations